Enriching Efl Learners’ Vocabulary Through Word Wall For Seventh Grade at SMPN 3 Abab - Yesin Erlin; Nike Angraini; Jaya Nur Iman (CV. ULIL ALBAB CORP, 2025)
Students around the world often face challenges in expanding their vocabulary in a second or foreign language. Common obstacles include understanding complex vocabulary, difficulty in pronunciation, and difficulty remembering new words. Cultural factors, learning environment, and teaching methods can also affect students' vocabulary acquisition. Vocabulary is one of the aspects present in most language skills such as listening, speaking, reading, and writing when learning English as a second language. In this study, the researcher employed this design to evaluate the effectiveness of the